2007
DOI: 10.1890/06-0502
|View full text |Cite
|
Sign up to set email alerts
|

Microbe‐mediated Plant–soil Feedback Causes Historical Contingency Effects in Plant Community Assembly

Abstract: Abstract. Plant-soil feedback affects performance and competitive ability of individual plants. However, the importance of plant-soil feedback in historical contingency processes and plant community dynamics is largely unknown. In microcosms, we tested how six earlysuccessional plant species of secondary succession on ex-arable land induced plant-specific changes in soil community composition. Following one growth cycle of conditioning the soil community, soil feedback effects were assessed as plant performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
445
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(472 citation statements)
references
References 68 publications
24
445
0
3
Order By: Relevance
“…Plant-soil microbiota feedbacks can influence plant species diversity, relative abundance patterns, community succession and species invasions (Klironomos 2002;Wolfe & Klironomos 2005;Kardol, Bezemer & van der Putten 2006;Kardol et al 2007;Rudgers, Fischer & Clay 2010). If plant species differ in the soil communities they cultivate and in their response to those communities in non-transitive ways, then these relationships could result in intransitive competitive networks among plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Plant-soil microbiota feedbacks can influence plant species diversity, relative abundance patterns, community succession and species invasions (Klironomos 2002;Wolfe & Klironomos 2005;Kardol, Bezemer & van der Putten 2006;Kardol et al 2007;Rudgers, Fischer & Clay 2010). If plant species differ in the soil communities they cultivate and in their response to those communities in non-transitive ways, then these relationships could result in intransitive competitive networks among plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the enemy release hypothesis proposes that the success of invasive species can be explained by their release from natural enemies found in their native range (Keane and Crawley 2002). Recent studies that investigated interactions between plants and soil organisms observed that negative feedbacks play a significant role in plant performance in mixed grassland communities (Bever 1994, Bever et al 1997, Klironomos 2002, Kardol et al 2007, Petermann et al 2008, Harrison and Bardgett 2010. Negative soil feedbacks can enhance species coexistence due to a form of a Janzen-Conell effect (Bever et al 1997, Packer and Clay 2000, Petermann et al 2008, McCarthy-Neumann and Kobe 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies concerning nutrient cycling PSF often neglected the roles of microbial decomposers in controlling the soil nutrient pool size, except some studies on microbial pathogens and symbionts that directly interact with plants (10)(11)(12)(13)(14)(15). However, recent studies in microbial ecology have started to challenge this plantcentered view of plant-soil systems.…”
mentioning
confidence: 99%